Optogenetic‐mediated cardiovascular differentiation and patterning of human pluripotent stem cells. Issue 3 (10th September 2021) - Hellwarth, Peter B.; Chang, Yun; Das, Arundhati; Liang, Po‐Yu; Lian, Xiaojun; Repina, Nicole A.; Bao, Xiaoping
Abstract: Precise spatial and temporal regulation of dynamic morphogen signals during human development governs the processes of cell proliferation, migration, and differentiation to form organized tissues and organs. Tissue patterns spontaneously emerge in various human pluripotent stem cell (hPSC) models. However, the lack of molecular methods for precise control over signal dynamics limits the reproducible production of tissue patterns and a mechanistic understanding of self‐organization. We recently implemented an optogenetic‐based OptoWnt platform for light‐controllable regulation of Wnt/β‐catenin signaling in hPSCs for in vitro studies. Using engineered illumination devices to generate light patterns and thus precise spatiotemporal control over Wnt activation, here we triggered spatially organized transcriptional changes and mesoderm differentiation of hPSCs. In this way, the OptoWnt system enabled robust endothelial cell differentiation and cardiac tissue patterning in vitro . Our results demonstrate that spatiotemporal regulation of signaling pathways via synthetic OptoWnt enables instructive stem cell fate engineering and tissue patterning. Abstract :